Pengaruh Intensitas Persediaan, Ukuran Perusahaan Dan CSR Terhadap Agresivitas Pajak Dengan Koneksi Politik Sebagai Variabel Moderasi - Puspita, Mega Gita (PT Wim Solusi Prima, 2024)
Tax aggressiveness is a form of income design practice carried out by companies to minimize taxes that must be paid illegally. The percentage of tax aggressiveness actions taken by manufacturing companies reaches 23%. This study aims to determine and analyze tax aggressiveness with koneksi politiks as a moderating variable, which is known to be closely related to aggressive corporate tax avoidance activities. The independent variables used in this study are inventory intensity, company size, and corporate social responsibility (CSR). This study uses descriptive quantitative methods and purpsive sampling, while the data collection uses secondary data in the form of financial reports and company annual reports. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The study population was 368 companies with a sample acquisition of 80 data and a total observation of 240 data over a 3-year period. The data analysis method uses multiple linear regression and moderated analysis regression (MRA) and data processing using SPSS 24. The results of this study indicate that inventory intensity and CSR have no effect on tax aggressiveness, company size has a positive effect on tax aggressiveness, koneksi politiks are unable to moderate inventory intensity and CSR on tax aggressiveness, koneksi politiks are able to moderate company size on tax aggressiveness.